2019
DOI: 10.1002/jor.24408
|View full text |Cite
|
Sign up to set email alerts
|

Nonviral Transfection With Brachyury Reprograms Human Intervertebral Disc Cells to a Pro‐Anabolic Anti‐Catabolic/Inflammatory Phenotype: A Proof of Concept Study

Abstract: Intervertebral disc (IVD) degeneration is a major contributor to chronic low back pain and is characterized by decreases in cellularity and proteoglycan synthesis, upregulation of matrix degradation, and increases in pro‐inflammatory factors with neurovascular invasion. Current treatments fail to target the underlying pathology or promote tissue repair and approaches such as viral transfection raise safety concerns due to mutagenesis and unwarranted immune responses. To avoid such concerns, nonviral transfecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 24 publications
(49 citation statements)
references
References 51 publications
3
46
0
Order By: Relevance
“…From early organogenesis, its expression is restricted to axial mesoderm/notochord lineage and further maintained after birth in NC constituting the NP, the core of the IVD, in mouse and in human [64,65]. In a recent report, T-encoding plasmid transfection was shown to reprogram mildly degenerate human CLC in vitro to a healthy NP-like phenotype with increased expression of key NP markers and significant proteoglycan/glycosaminoglycan accumulation [66]. Another interesting study also used T-encoding plasmid transfection to differentiate hiPSCs toward an NLC phenotype capable of synthesizing a proteoglycan-rich matrix and playing a protective role in the catabolic environment of injury-induced porcine disc model [67].…”
Section: Discussionmentioning
confidence: 99%
“…From early organogenesis, its expression is restricted to axial mesoderm/notochord lineage and further maintained after birth in NC constituting the NP, the core of the IVD, in mouse and in human [64,65]. In a recent report, T-encoding plasmid transfection was shown to reprogram mildly degenerate human CLC in vitro to a healthy NP-like phenotype with increased expression of key NP markers and significant proteoglycan/glycosaminoglycan accumulation [66]. Another interesting study also used T-encoding plasmid transfection to differentiate hiPSCs toward an NLC phenotype capable of synthesizing a proteoglycan-rich matrix and playing a protective role in the catabolic environment of injury-induced porcine disc model [67].…”
Section: Discussionmentioning
confidence: 99%
“…The effect of transfecting GDF6 was examined using this protocol and system; however, due to potential limitations with the specific GDF6 plasmid used, no increase in ECM proteins could be observed. Tang et al used this same Neon transfection system to examine the effect of electroporating developmental transcription factor Brachyury into human nucleus pulposus cells from cadavers and patients undergoing surgery for low back pain in 3D in vitro culture (Tang S. et al, 2019). In this study, significant increases in Brachyury were observed up to 4 weeks, together with improvements in IVD phenotypic markers FOXF1, KRT19, and SOX9 and decreases in inflammatory/catabolic/pain markers IL1−β, IL-6, NGF, and MMP-13 compared to transfected sham vector control cells.…”
Section: Physical Gene Vector Methods For the Intervertebral Diskmentioning
confidence: 99%
“…Electroporation (Gehl, 2003;Wells, 2004;Glover et al, 2005;Mehier-Humbert and Guy, 2005;Liu et al, 2006;Al-Dosari and Gao, 2009;Boukany et al, 2011;Guo and Huang, 2012;Mellott et al, 2013;Song et al, 2015;Tschon et al, 2016;Tsuchiya et al, 2017;Vroomen et al, 2017;Kawai et al, 2018;Melancon et al, 2018;Shapiro et al, 2018;Shi B. et al, 2018;Tang S. et al, 2019;Bono et al, 2020) Rapid and straightforward transfection method.…”
Section: Advantages Limitations Applicationsmentioning
confidence: 99%
See 2 more Smart Citations